Design and Testing of radiofrequency instrument Ronja ICS - Grepl, Jan; Vavra, Petr; Ihnat, Petr; Hlavackova, Milada; Penhaker, Marek; Krest'anova, Alice; Kubicek, Jan (2019 IEEE 17th World Symposium on Applied Machine Intelligence and Informatics (SAMI), 2019)
The application of radiofrequency energy to the hepatic tissue is currently a unique opportunity to solution problem of trauma and tumor tissues. With the increasing incidence of colorectal cancer and with successful oncology treatments, the number of potential patients with hepatic metastases is increasing. Using the new methods and instruments in surgical therapy, it can greatly improve the quality of life of these patients. The proposed RONJA ICS semispherical bipolar radiofrequency instrument enables fast coagulation of subsurface and surface hepatic tissue for ablation of neoplasms. This device allows to reduce the amount of tissue removed in the liver during surgery, which was confirmed in preclinical tests. When performing a resection of hepatic tissue using a new semispherical device, it was also confirmed that this new method is effective and safe.